Color Coded Cards for Student Behavior Management in Higher Education Environments - Alhalabi, Wadee S.; Alhalabi, Mobeen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
The Color Coded Cards system as a possibly effective class management tool is the focus of this research. The Color Coded Cards system involves each student being given a card with a specific color based on his or her behavior. The main objective of the research is to find out whether this system effectively improves students’ behavior, thus leading to better class management. The research was conducted with 350 students as subjects, and the data were gathered by means of a questionnaire administered over a period of three years. A qualitative method was applied to analyze the results and draw precise conclusions. The results were interesting and promising.